2005
DOI: 10.1089/dna.2005.24.225
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Changes in the Subcellular Localization of the Nuclear Protein–Tyrosine Kinase, c-Fes

Abstract: Tyrosine phosphorylation has emerged as a mechanism to control cellular events in the nucleus. The c-Fes protein-tyrosine kinase is an important regulator of cell growth and differentiation in several cell types, and is found in the nucleus of hematopoietic cells. In this study, we showed nuclear localization of c-Fes in both hematopoietic (K562, TF-1, HEL, U937, and HL-60) and nonhematopoietic cell lines (293T, CaOv3, TfxH, MG-63, HeLa, DU-145) by immunofluorescence and confocal microscopy. c-Fes showed strik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…In this regard, it is recognized that phosphorylation of proteins is an important mechanism that controls cellular events in the nucleus. 36 These data indicate that some form of alternative signaling and/or crosstalk between pathways is in play, adding support to the suggestion that the GR is present in a range of multiprotein complexes (receptosomes) with different functions and means of gene regulation. 37 Clearly, a future study is warranted to understand the effects of dexamethasone on OPN gene regulation, because GR-interacting protein complexes may play a role in the variability of glucocorticoid responsiveness observed in some patients.…”
Section: Kirton Et Al Dexamethasone Accelerates Pericyte Differentiationsupporting
confidence: 57%
“…In this regard, it is recognized that phosphorylation of proteins is an important mechanism that controls cellular events in the nucleus. 36 These data indicate that some form of alternative signaling and/or crosstalk between pathways is in play, adding support to the suggestion that the GR is present in a range of multiprotein complexes (receptosomes) with different functions and means of gene regulation. 37 Clearly, a future study is warranted to understand the effects of dexamethasone on OPN gene regulation, because GR-interacting protein complexes may play a role in the variability of glucocorticoid responsiveness observed in some patients.…”
Section: Kirton Et Al Dexamethasone Accelerates Pericyte Differentiationsupporting
confidence: 57%
“…6i–l). Nuclear localization has deen reported for FES in other cell types, and its sub-cellular localization is thought to vary depending on the cell type and/or stage of cell cycle 69 . Significant expression of PlexinB1 and Crmp2 was detected in the RNA-Seq libraries of both Tas1r3 + and type III cells.…”
Section: Resultsmentioning
confidence: 99%
“…The subcellular localization of FER in the oocyte has parallels in somatic cells. For example, FER kinase contains an atypical nuclear localization signal within the kinase region (Ben‐Dor et al, 1999) and the closely related FES kinase was reported to translocate from the nucleus of interphase somatic cells and to the cytoplasm during prometaphase (Carlson et al, 2005). In addition, FER tagged with green fluorescent protein (GFP)‐FER and GFP‐FES have been localized to spindle microtubules in mitotic cells, suggesting that this kinase family is capable of a specific interaction with microtubules (Kogata et al, 2003; Laurent et al, 2004).…”
Section: Discussionmentioning
confidence: 99%